2019
DOI: 10.1128/jvi.00124-19
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Virus Antagonizes NOD2-Mediated Antiviral Effects by Inhibiting NOD2 Protein Expression

Abstract: The role of nucleotide-binding oligomerization domain 2 (NOD2) in foot-and-mouth disease virus (FMDV)-infected cells remains unknown. Here, we showed that FMDV infection activated NOD2-mediated beta interferon (IFN-␤) and nuclear factor-B (NF-B) signaling pathways. NOD2 inhibited FMDV replication in the infected cells. FMDV infection triggered NOD2 transcription, while it reduced the abundance of NOD2 protein. Our results revealed that FMDV 2B, 2C, and 3C proteinase (3C pro ) were responsible for the decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 68 publications
0
37
0
Order By: Relevance
“…Another study showed that FMDV 2B protein interacts with NOD2 to reduce the expression of NOD2 protein, for which the 2B carboxyl-terminal 105-114 region was essential, thus inhibiting the activation of NF-κB and IFN-β signaling pathways (Figure 3, Table 2). The decrease in NOD2 is not related to the cleavage of EIF4G, induction of apoptosis or proteasome, nor lysosome or caspase pathways [16].…”
Section: Bmentioning
confidence: 76%
See 3 more Smart Citations
“…Another study showed that FMDV 2B protein interacts with NOD2 to reduce the expression of NOD2 protein, for which the 2B carboxyl-terminal 105-114 region was essential, thus inhibiting the activation of NF-κB and IFN-β signaling pathways (Figure 3, Table 2). The decrease in NOD2 is not related to the cleavage of EIF4G, induction of apoptosis or proteasome, nor lysosome or caspase pathways [16].…”
Section: Bmentioning
confidence: 76%
“…However, the exact mechanism of governing vimentin cage formation and dissolution remains to be elucidated [108]. The interaction between FMDV protein 2C and NOD2 reduces the level of NOD2 protein to help the virus evade the immune response, and the carboxyl-terminal 116-209 and 210-260 regions of 2C were essential for the interaction [16] (Figure 3, Table 2). Strikingly, the interaction between 2C and Beclin1 or NOD2 evades immune response through different pathways, which contributes to the replication of FMDV.…”
Section: Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, 2B can decrease the expression levels of MDA5 and RIG-I followed by disrupting the phosphorylation of key factors TBK1 and IRF3, thereby inhibiting the IFN-β production in the RLRs antiviral signaling pathway ( Zhu et al, 2016 ; Li et al, 2018 ). Recent study has demonstrated that 2B affects the NF-κB and IFN-β signaling pathway by downregulating nucleotide-binding oligomerization domain 2 (NOD2) expression to enhance FMDV replication ( Liu et al, 2019 ). In addition, interaction of 2B with the host Cyclophilin A (CypA) reduced CypA-mediated degradation of L pro to promote FMDV replication ( Liu et al, 2018 ).…”
Section: Fmdv Proteins Regulate Host Innate Immunitymentioning
confidence: 99%